THERMOTOLERANCE BEHAVIOR IN SUGAR-CANE SYRUP FERMENTATIONS OF WILD-TYPE YEAST STRAINS SELECTED UNDER PRESSURES OF TEMPERATURE, HIGH SUGAR AND ADDED ETHANOL - Laluce, Cecília [UNESP]; Abud, C. L.; Greenhalf, W.; Sanchesperes, M. F. (Chapman Hall Ltd, 1993)
The selected yeast strains were examined for their ability lo grow, to retain cell viability and to ferment diluted sugar cane juice (15% total sugar, w/v) to ethanol at 40-degrees-C. The degree of agitation (aeration) affects the thermotolerance while the method used for isolation of the strains appears to have no significant effect. The yeast isolated are aerobically fermentative with increased levels of fermentation and growth resulting from agitation (aeration), the exact level of these increases being dependent on the strain used.